Australian Aboriginal and Torres Strait Islander-focused primary healthcare social and emotional wellbeing research: a systematic review protocol. Issue 1 (December 2015) - Farnbach, Sara; Eades, Anne-Marie; Hackett, Maree
Abstract Background Research with a focus on Aboriginal and Torres Strait Islander Australian's (hereafter referred to as Indigenous1 ) needs is crucial to ensure culturally appropriate evidence-based strategies are developed to improve health. However, concerns surrounding this research exist, arising from some previous research lacking community consultation, resulting in little community benefit or infringing on important cultural values.Values and Ethics :Guidelines for Ethical conduct in Aboriginal and Torres Strait Islander Health Research (hereafter referred to as Values and Ethics), developed by The National Health and Medical Research Council of Australia in 2003, is the ethical standard for Indigenous-focused health research. Researchers must address its Values in research design and conduct. However, its impact on research processes is unclear. Local Protocols should also be considered. This review aims to systematically examine practices related to Values and Ethics, Local Protocols and the processes of conducting Indigenous-focused primary healthcare research in collaboration with external researchers. Methods The following electronic databases and grey literature will be searched (2003 to current): MEDLINE, EMBASE, CINAHL, Informit and HealthInfoNet—an Indigenous-specific research and program website. Indigenous-focused research will be included. Research must be conducted in one or more primary healthcare services, in collaboration with external researchers and with a focus on social and emotional well being. One reviewer will review titles and abstracts to remove obviously irrelevant research articles. Full-text research articles will be retrieved and independently examined by two reviewers. Data and quality assessment will be completed by one reviewer and verified by a second reviewer. Quality will be assessed using modified versions of established quality assessment tools. Discussion This review will provide information on research processes and the impact of Values and Ethics on Indigenous-focused primary healthcare research, informing communities and primary healthcare staff around research practices, and researchers and policy makers of strengths and weaknesses of practice. Systematic review registration PROSPEROCRD42015024994